Climate Resilient Agriculture Strategies and Perspectives - Srinivasa Rao, Ch; Shanker, Arun K.; Shanker, Chitra (IntechOpen, 2018)
The changing climatic scenario has affected crop production in the adverse ways, and the impact of it on agriculture is now emerging as a major priority among crop science researchers. Agriculture in this changing climatic scenario faces multiple diverse challenges due to a wide array of demands. Climate-resilient agriculture is the need of the hour in many parts of the world. Understanding the adverse effects of climatic change on crop growth and development and developing strategies to counter these effects are of paramount importance for a sustainable climate-resilient agriculture. This multiauthored edited book brings out sound climate-resilient agriculture strategies that have a strong basic research foundation. We have attempted to bridge information from various diverse agricultural disciplines, such as soil science, agronomy, plant breeding, and plant protection, which can be used to evolve a need-based technology to combat the climatic change in agriculture.